1. The problem statement, all variables and given/known data Prove that (1+cosA - sinA)/(1+cosA + sinA) = secA - tanA 2. Relevant equations sin^2A + cos^2A = 1 tanA = sinA/cosA cotA = cosA/sinA 1 + cot^2A = cosec^2A tan^2A + 1 = sec^2A cosecA = 1/sinA secA = 1/cosA cotA = 1/tanA (Only use the above identities to prove the question) 3. The attempt at a solution I'm stumped at this question. I have attempted various methods using the formulas that I know(stated above)and also trying to work on both sides but to no avail. I understand that by cross multiplying we can easily prove it but the correct way seems to just be by making either the LHS or RHS equal to the other,respectively. Can anyone help?